Extramedullary plasmacytoma nose operated by raveh’s approach: a case report - Kaur, Ramandeep; Arora, Vipin; Taneja, H. C.; Sharma, Abhimanyu (International Surgery Journal, 2017)
Plasmacytoma is a clonal proliferation of plasma cells. Plasmacytoma can be disseminated in the form of multiple myeloma or solitary disease. Most common site of involvement of solitary extramedullary plasmacytoma being the upper respiratory tract. We present a case report of 60-year-old male who presented with bilateral nasal obstruction, epistaxis and swelling on the root of nose. Biopsy proved out to be a plasmacytoma which was operated by Raveh’s approach. Raveh’s approach is a very useful approach for skull base tumors in the sphenoethmoidal plane with minimal morbidity, no frontal lobe retraction and watertight closure of dura and excellent postoperative recovery.